AKIBAT HUKUM RATIFIKASI OPTIONAL PROTOCOL ON THE CONVENTION AGAINST TORTURE (OPCAT) DAN PENGARUHNYA PADA PERLINDUNGAN HAK ATAS RASA AMAN DARI PENYIKSAAN DI INDONESIA - Ardya, Naura (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Abstract: Optional Protocol on the Convention Against Torture (OPCAT) is an international agreement that aims to prevent torture and other ill-treatment by establishing a system consisting of conducting regular visits to all places of detention in participating countries. The OPCAT is not only an instrument that determines a certain standard, but as an implementation treaty which is a follow-up agreement from the Convention against Torture (UNCAT). Indonesia has ratified the convention into Law no. 5 of 1998. However, until this research was conducted, efforts to ratify the OPCAT had not been successful. This research will contain the legal consequences and implications if Indonesia ratifies the OPCAT and how it affects the protection of the right to feel safe from torture for children in Indonesia. This research is a normative research that uses a conceptual approach, cases, and laws and regulations and is analyzed by collecting secondary data through library research.